Risk Factors Associated With Long-Term Hospitalization in Patients With COVID-19: A Single-Centered, Retrospective Study - Wu, Yiqun; Hou, Bingbo; Liu, Jielan; Chen, Yingying; Zhong, Ping (Frontiers in Medicine, 2020)
Background: The coronavirus disease 19 (COVID-19) pandemic has become a global threat. Few studies have explored the risk factors for the recovery time of patients with COVID-19. This study aimed to explore risk factors associated with long-term hospitalization in patients with COVID-19. Methods: In this retrospective study, patients with laboratory-confirmed COVID-19 hospitalized in a hospital in Wuhan by March 30, 2020, were included. Demographic, clinical, laboratory, and radiological data from COVID-19 patients on hospital admission were extracted and were compared between the two groups, defined as short- and long-term hospitalization, respectively according to the median hospitalization time. Univariable and multivariable logistic regression methods were performed to identify risk factors associated with long-term hospitalization in patients with COVID-19. Results: A total of 125 discharged patients with COVID-19 were reviewed, including 123 general patients and two severe patients. The median hospitalization time was 13.0 days (IQR 10.0–17.0). Among them, 66 patients were discharged <14 days (short-term group) and 59 patients were discharged ≥14 days (long-term group). Compared with the short-term group, patients in the long-term group had significantly higher levels of C-reactive protein (P = 0.000), troponin I (P = 0.002), myoglobin (P = 0.037), aspartate aminotransferase (P = 0.005), lactic dehydrogenase (P = 0.000), prothrombin time (P = 0.030), fibrinogen (P = 0.000), and D-dimer (P = 0.006), but had significantly lower levels of lymphocyte count (P = 0.001), platelet count (P = 0.017), albumin (P = 0.001), and calcium (P = 0.000). Additionally, the incidences of hypocalcemia (P = 0.001), hyponatremia (P = 0.021), hypochloremia (P = 0.019), and bilateral pneumonia (P = 0.000) in the long-term group were significantly higher than those in the short-term group. Multivariable regression showed that hypocalcemia (P = 0.007, OR 3.313, 95% CI 1.392–7.886), hypochloremia (P = 0.029, OR 2.663, 95% CI 1.104–6.621), and bilateral pneumonia (P = 0.009, OR 5.907, 95% CI 1.073–32.521) were independent risk factors associated with long-term hospitalization in patients with COVID-19. Furthermore, a ROC curve where the area under the ROC was 0.766 for retained variables is presented. Conclusions: Hypocalcemia, hypochloremia, and bilateral pneumonia on hospital admission were independent risk factors associated with long-term hospitalization in patients with COVID-19. To the best of our knowledge, this is the first study to highlight the importance of electrolyte imbalance in predicting the hospitalization time of patients with COVID-19.